HIV/AIDS Stigma and Discrimination: A Canadian Perspective and Call to Action - Josephine M. MacIntosh (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2007)
Canada as a nation is committed to addressing HIV/AIDS stigma and discrimination. The federal government hasrecently announced that funding for HIV prevention, care and treatment will double by 2009, from a current $42.2million to $84.4 million. While the prevalence of HIV/AIDS in Canada is relatively low, experiences of HIV/AIDSstigma and discrimination are common. In response to this situation, the Canadian HIV/AIDS Legal Network hasrecently released a report outlining a series of goals and actions designed to prevent, reduce and eliminate HIV/AIDSstigma and discrimination. By promoting tolerance and understanding through research, legislation and community levelaction we can diminish the overarching epidemic of stigma and discrimination and decrease the extent of the HIVepidemic in Canada.